2021
DOI: 10.52547/jarums.20.2.280
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Multidrug-resistant Pseudomonas aeruginosa Strains in Ardabil

Abstract: Background & objectives: Bacterial antibiotic resistance is becoming a global health crisis. The aim of this descriptive, cross-sectional study was to investigate the prevalence of multidrug-resistant Pseudomonas aeruginosa strains in Ardabil. Methods: During 9 months, between July 2019 and March 2020, 50 strains of Pseudomonas aeruginosa were collected from different clinical specimens in four hospitals of Ardabil and the prevalence of MDR, XDR and PDR strains of Pseudomonas aeruginosa were evaluated. Antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Bacterial isolates were collected from different specimens of patients who were referred to Ardabil hospitals from June 2019 to February 2021. The collected isolates were confirmed by standard laboratory tests, including pigment production, Gram-staining, catalase, and oxidase, as well as species-specific PCR (10). Confirmed bacteria were tested to identify imipenem resistance and MBL-positive isolates using phenotypic and genotypic methods.…”
Section: P Aeruginosa Isolatesmentioning
confidence: 99%
“…Bacterial isolates were collected from different specimens of patients who were referred to Ardabil hospitals from June 2019 to February 2021. The collected isolates were confirmed by standard laboratory tests, including pigment production, Gram-staining, catalase, and oxidase, as well as species-specific PCR (10). Confirmed bacteria were tested to identify imipenem resistance and MBL-positive isolates using phenotypic and genotypic methods.…”
Section: P Aeruginosa Isolatesmentioning
confidence: 99%
“…Our study's findings were similar to those of Farva and Bhutta (2021), who reported a prevalence of 30%, and Ijaz et al (2019), who reported a prevalence of 38%, but they were lower than those of Nasser et al (2018), who reported a prevalence of 46%. Several classes of antibiotics have been described as being utilized as antipseudomonas medications in various research (Nasser et al, 2018;Bazghandi et al, 2020;Abdulhaq et al, 2020). We used the following antibiotics in this study: imipenem (10 g), meropenem (10 g), cefepime (30 g), ciprofloxacin (5 g), amikacin (30 g), ceftriaxone (30 g), ceftazidime (30 g), and gentamycin (10 g).…”
Section: Synergistic Effect Of Agnps With Drugsmentioning
confidence: 99%